Politics and the New African Novel: A Study of the Fiction of Francis Bebey - W. Curtis Schade (Studies in 20th & 21st Century Literature, 1980)
From its inception African fiction has been strongly marked by political themes. In the late 1950's the virulent satire of Mongo Béti and Ferdinand Oyono stated the case against the denigration of African values inherent in all aspects of the colonial system. Their style and message subsequently gave way to novels focusing upon the drama of the transition of power at the moment of Independence. Whether optimistic or disillusioned, many of these novels featured real events and people, often thinly disguised, and sought to give an «inside» picture of that historical moment. Other tendencies developed in the late 60's, most notably a strongly autocritical, often radical, body of fiction represented by such writers as Ousmane Sembène and Alioum Fangouré, and the more distant, philosophical study of politics and society of writers like Ahmadou Kourouma. In all of these examples the contemporary political situation, whether viewed globally or as it affected the life of a simple man, was the primary moving force within the novel. By contrast, this paper will concentrate upon the work of Francis Bebey, exemplary of another current trend, fiction which, while continuing to deal with political concerns, does so in a different light, creating different tones, using different techniques. In the three novels and one short-story studied, politics is subordinated to other concerns and is treated less reverently than heretofore. We see in the work of Bebey a re-assessment of politics and its place in the life of contemporary (African) man.
Keywords: African fiction; Africa; novel; political; Mongo Béti; Ferdinand Oyono; African values; colonialism; Independence; real events; autocritical; radical; Ousmane Sembène; Alioum Fangouré; Ahmadou Kourouma; Francis Bebey; short-story; contemporary man; African man; man